Demographic variables and childhood obesity in a community-based program in Portugal - Silva, Ana Lúcia (2012)
INTRODUCTION: The prevalence of overweight and obesity have been increasing consistently throughout the European Union, especially in Portugal, affecting everyday a higher number of children and adolescents. A community-based program in health promotion can identify the main areas of action for the protection of the population against health threats and the promotion of guidelines that can lead to healthier life-styles. Adequate urban environments could be one of the main areas of action for obesity prevention. METHODS: This study is framed from a longitudinal municipal project (MUNSI), which included 3173 children (6-9 years old) from 167 public schools. Childhood obesity was assessed by anthropometric parameters (weight and height) considering the Centers for Disease and Control and Prevention (CDC) growthcharts criteria of percentiles of Body Mass Index (BMI). Demographic variables (typology of urban area and familiy household) were collected by a self-response family questionnaire. The Odds Ratio was calculated with a 95% Confidence Intervals. RESULTS: Children who lived in urban areas showed higher obesity prevalence (14.6%) compared with those residing in rural areas (13.3%) associated also with higher odds (OR= 1.15; 0.8-1.66). According to Family household, single child families showed higher obesity prevalence (17.1%) with a OR=1.6 (1.1 - 2.3) compared to families who had more than one child. CONCLUSION: Environmental factors such the typology of urban area and family household should be considered important contributing factors for childhood obesity. Future research should attempt to quantify and elucidate, more precisely, the epidemiology of these conditions